2017
DOI: 10.1513/annalsats.201701-062sr
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Nasal Nitric Oxide Measurement as a Diagnostic Test for Primary Ciliary Dyskinesia: A Systematic Review and Meta-Analysis

Abstract: a b s t r a c tAim: Extracorporeal resuscitation during cardiopulmonary resuscitation (ECPR) deploys rapid cardiopulmonary bypass to sustain oxygenated circulation until the return of spontaneous circulation (ROSC). The purpose of this systematic review is to address the defining elements and outcomes (quality survival and organ donation) of currently active protocols for ECPR in refractory out-of-hospital cardiac arrest (OHCA) of cardiac origin in adult patients. The results may inform policy and practices fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 74 publications
1
45
0
2
Order By: Relevance
“…Nitric oxide (NO) is a small diffusible gas molecule that is involved in multiple functions throughout the body. Multiple studies have demonstrated that nitric oxide within the nasal cavity (particularly within the sinuses) is high in healthy individuals and much lower (<10% of normal values) in PCD, suggesting that nasal NO (nNO) measurement may be a useful test for PCD [29,84,88,135]. Nasal NO is measured by a non-invasive approach using a small nasal probe to aspirate nasal gas at a rate of approximately 5 ml/second for measurement of nitric oxide content [10,14].…”
Section: Nasal Nitric Oxide Testingmentioning
confidence: 99%
“…Nitric oxide (NO) is a small diffusible gas molecule that is involved in multiple functions throughout the body. Multiple studies have demonstrated that nitric oxide within the nasal cavity (particularly within the sinuses) is high in healthy individuals and much lower (<10% of normal values) in PCD, suggesting that nasal NO (nNO) measurement may be a useful test for PCD [29,84,88,135]. Nasal NO is measured by a non-invasive approach using a small nasal probe to aspirate nasal gas at a rate of approximately 5 ml/second for measurement of nitric oxide content [10,14].…”
Section: Nasal Nitric Oxide Testingmentioning
confidence: 99%
“…ниже) и оцен-ка по предиктивной шкале PICADAR 1 для выявления признаков первичной цилиарной дискинезии у паци-ентов, имеющих хронические респираторные симпто-мы с раннего детского возраста >5 баллов (табл. 1) [7]; • результаты скрининга: исследование уровня оксида азота (NO) в выдыхаемом назальном воздухе (у пода-вляющего большинства пациентов с ПЦД он снижен [8]), при этом до настоящего времени нет единого мне-ния о референсных положительных и отрицательных значениях данного показателя у пациентов с ПЦД. При отсутствии возможности измерения оксида азота в назальном выдыхаемом воздухе допустимо в каче-стве ориентировочного скрининга использовать мето-дики определения оксида азота в выдыхаемом возду-хе, в т.ч.…”
Section: классификацияunclassified
“…Epitelyal silyalarda dynein kollarının olmaması elektron mikroskopik incelemede en sık görülen bozukluktur (8). Çocukluk çağında kronik otosinopulmoner enfeksiyon geçirenler hastalarda tarama testi olarak düşük nasal nitrik oksit seviyeleri kullanılsa da tanı koydurucu test olarak elektron mikroskopisi ve genetik testleriyle doğrulanmasına ihtiyaç duymaktadır (9). Hastanın sinüzit, bronşiektazi ve situs inversus triadını sağlamasıyla Kartagener Sendromu tanısı konuldu.…”
Section: Introductionunclassified